The Effect of Moringa (Moringan Oleifera) Leaf Powder on Maternal Knowledge with Stunting Prevention in Drien Rampak Village - Fitri Apriani; Orita Satria; Siti Damayanti; Harwalis; Yulia Aulia; Dian Vita Sari (Journal of Health Empowerment and Interprofessional Practice, 2025)
Background of study: Stunting is a condition where toddlers don't grow properly because they don't get enough nutrition over a long time, get sick often, and don't get enough mental stimulation. One way to prevent stunting is by using Moringa leaves. However, many parents don't know much about the benefits of Moringa leaves, so it's important to educate them so they understand better. Aims and scope of paper: This study aimed to find out how giving Moringa leaf powder to mothers affects their knowledge about preventing stunting in Drean Rampak Village. Method: This research used a quantitative design with a quasi-experimental approach, specifically a one-group pretest-posttest design. The study took one month, from August 1 to September 1, 2024, and included 49 participants. It used the Wilcoxon test for analysis of the data. Results: The study found that giving Moringa leaf powder had a big effect on mothers' knowledge about preventing stunting, with a p-value of 0.000, which is less than the significance level of 0.05, and a z-value of -6.285b. Conclusion: The results show that giving Moringa leaf powder helps improve mothers' knowledge about preventing stunting in Drean Rampak Village, West Aceh. More promotion and education about stunting and the benefits of Moringa leaves are needed to help reduce the number of children who are stunted.